Climate change impacts on Great Lakes Basin precipitation extremes. Issue 18 (27th September 2014) - d'Orgeville, Marc; Peltier, W. Richard; Erler, Andre R.; Gula, Jonathan
Abstract A physics‐based miniensemble of Weather Research and Forecasting model simulations of climate change over the Great Lakes Basin has been constructed, by dynamically downscaling a single global Community Earth System Model 1 simulation driven by the Representative Concentration Pathways 8.5 scenario. The analysis pipeline is successfully verified by comparison of the results with observations for the historical period (1979–1994) and then applied to produce future projections (2045–2060). By midcentury, in this miniensemble, the future change in rainfall distribution is projected to correspond to an increase of total rainfall (median increase of between 13 and 19%) characterized by a fattening of the tail of the distribution (median increase of between 14 and 29% of the amplitude of a 50 year extreme rainfall event). Average rainfall intensity changes are shown to accurately follow the "Clausius–Clapeyron" thermodynamically expected 7% increase per degree of surface warming, whereas heavy rainfall changes are found to lie between 7 and 10% per degree of surface warming. This further increase can be explained by two effects in the Great Lakes region: midtropospheric warming is projected to be larger than surface warming and heavy rainfall events are projected to originate from higher altitude where additional moisture is available. Details of the physics configuration play only a secondary role in determining the future precipitation changes, primarily through their impact on future temperature changes. The uncertainty in the future projection of precipitation and its extremes therefore depends primarily upon the uncertainty in projected future warming which will require implementation of a larger ensemble of projections to be more accurately assessed.